2013
DOI: 10.1186/1742-9994-10-69
|View full text |Cite
|
Sign up to set email alerts
|

Female mate choice in convict cichlids is transitive and consistent with a self-referent directional preference

Abstract: IntroductionOne of the most important decisions that an animal has to make in its life is choosing a mate. Although most studies in sexual selection assume that mate choice is rational, this assumption has not been tested seriously. A crucial component of rationality is that animals exhibit transitive choices: if an individual prefers option A over B, and B over C, then it also prefers A over C.ResultsWe assessed transitivity in mate choice: 40 female convict cichlids had to make a series of binary choices bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 104 publications
0
25
0
Order By: Relevance
“…Overall, although direct evidence for active and rational choice is still lacking (Bateson and Healy 2005;Reaney 2009;Dechaume-Moncharmont et al 2013), our results suggest that body size and heterozygosity may affect mutual mate choice in Zenaida doves, although not necessarily in the same fashion. In addition, our results indicate that patterns of mating in relation to absolute and relative genetic quality may vary depending on how heterozygosity affects fitness in natural populations.…”
Section: Discussionmentioning
confidence: 58%
“…Overall, although direct evidence for active and rational choice is still lacking (Bateson and Healy 2005;Reaney 2009;Dechaume-Moncharmont et al 2013), our results suggest that body size and heterozygosity may affect mutual mate choice in Zenaida doves, although not necessarily in the same fashion. In addition, our results indicate that patterns of mating in relation to absolute and relative genetic quality may vary depending on how heterozygosity affects fitness in natural populations.…”
Section: Discussionmentioning
confidence: 58%
“…Despite the evolutionary importance of mate choice, studies of animal rationality have primarily focused on foraging behaviour78 or social dominance hierarchies13. Transitive mate choice is very rarely discussed or considered in sexual selection research and, to our knowledge, transitivity of mate choice in animals has only been tested twice1415 and has shown inconsistent results.…”
mentioning
confidence: 99%
“…Of the few tests that have been done on mate choice rationality141516, each presented females with potential mates that differed in traits affecting just one sensory modality. Yet, sexual displays are often complex, signalling to several different sensory modalities and differing in many ways within modalities17, and individuals of both sexes are faced with making mating decisions based on all of the information available rather than on single traits in isolation.…”
mentioning
confidence: 99%
“…Meanwhile, other studies have found support for transitive female mate choice. Dechaume‐Moncharmont, Freychet, Motreuil, and Cézilly () found that convict cichlid females were transitive in their preferences for males that varied in their size. Arbuthnott, Fedina, Pletcher, and Promislow () found that male mate choice for 10 isogenic lines of Drosophilia melanogaster was nearly perfectly transitive.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of rationality studies to date treat the population, not the individual, as the level of interest (for exceptions see Dechaume-Moncharmont et al, 2013;Shafir, 1994). For example, the Drosophilia study tested each male in a single binary test, not multiple tests, generating group-level preferences for each of the female lines instead of individual-level preferences (Arbuthnott et al, 2017).…”
mentioning
confidence: 99%